EUROPEAN OPTION PRICING WITH TGARCH-M(1,1) - (NIM: 10114035), HENDRY
Options is one of financial instruments that often included in investor's portfolio to protect their asset. Financial institutions and investors are required to valuate the prices with no arbritrage opportunity such that no one always win. The no arbitrage price helps their decision making. Black-Scholes formula is one of the model, but its assume constant volatility of stock return. Based on observation, stock return often exhibit volatility clustering property and fat-tailed distributed. Time series model Autoregressive Conditional Heteroskedasticity (Engle, 1982) and Generalized Autoregressive Conditional Heteroskedasticity (Bollerslev, 1986) capture the volatility clustering and allow us to innovate the distribution. TGARCH-M(1,1) is a variant of GARCH modified to capture the impact of news on stock return volatility and risk premium. Option pricing using TGARCH-M(1,1) model is better than Black-Scholes formula since the model describes the dynamics volatility of stock return. Finally, we use Generalized Error Distribution innovation in comparison to Gaussian innovation.